Grafted Neuronal Precursor Cells Differentiate and Integrate in Injured Hippocampus in Experimental Pneumococcal Meningitis12. (15th May 2012) - Hofer, Sandra; Magloire, Vincent; Streit, Jürg; Leib, Stephen L.
Abstract: Bacterial meningitis (BM) frequently causes persisting neurofunctional sequelae. Autopsy studies in patients dying from BM show characteristic apoptotic brain injury to the stem cell niche in the subgranular zone of the hippocampal dentate gyrus (DG), and this form of brain damage is associated with learning and memory deficits in experimental BM. With an eye to potential regenerative therapies, the survival, migration, and differentiation of neuronal precursor cells (NPCs) were evaluated after engraftment into the injured hippocampus in vitro and in vivo in an infant rat model of pneumococcal meningitis. Green fluorescent protein (GFP)‐expressing NPCs were grafted into the DG of organotypic hippocampal slice cultures injured by challenge with live Streptococcus pneumoniae . Seven days after engraftment, NPCs had migrated from the site of injection into the injured granular layer of the DG and electro‐functionally integrated into the hippocampal network. In vivo, GFP‐expressing NPCs migrated within 1 week from the injection site in the hilus region to the injured granular layer of the hippocampal DG and showed neuronal differentiation at 2 and 4 weeks after transplantation. Hippocampal injury induced by BM guides grafted NPCs to the area of brain damage and provides a microenvironment for neuronal differentiation and functional integration. STEM CELLS 2012;30:1206–1215